ANALISIS DAMPAK FEEDBACK FREAMING MEDIA SOSIAL DALAM PERSPEKTIF HUKUM BAGI NITIZEN DALAM KASUS VIRALNYA PEMKOT SURABAYA SIDAK PERUSAHAAN TAHAN IJAZAH KARYAWAN - Sirait, Timbo Mangaranap; Khalimi; Sendias, Nungky (The Juris, 2025)
The existence of media, both mass media and social media, has recently resulted in a very important role in influencing public opinion and is even considered as a media that will open all information that actually occurs in Indonesia and even in the world. There are many mass media and social media used as tools by political elites to influence public views on framing images for both personal and group image interests. Even the difference between the two is that social media has a more capable scope for the implementation of this function. Social media will play a greater role because with the existence of a container to accommodate freedom of opinion, netizens can freely provide feedback on their views as a reaction to the news that is rolling so that it increasingly shows the direction of various netizen reactions and increasingly emphasizes the direction of the reaction in the form of comments, uploads, reactions from other people's opinions and even influences real actions in the real world. Social media can shape our views on various issues that are rolling. One way that is often used by social media is by the way they "package" the news, which in simple terms is called "framing." Media framing can greatly influence the way we view an issue with the access that every social media user can obtain and can leave a trail of opinions written on the basis of freedom of speech.